Genetic population structure of endangered ring‐tailed lemurs (Lemur catta) from nine sites in southern Madagascar. Issue 15 (16th July 2020) - Chandrashekar, Aparna; Knierim, Jessica A.; Khan, Sohail; Raboin, Dominique L.; Venkatesh, Sateesh; Clarke, Tara A.; Cuozzo, Frank P.; LaFleur, Marni; Lawler, Richard R.; Parga, Joyce A.; Rasamimanana, Hantanirina R.; Reuter, Kim E.; et al.
Abstract: Madagascar's ring‐tailed lemurs ( Lemur catta ) are experiencing rapid population declines due to ongoing habitat loss and fragmentation, as well as increasing exploitation for bushmeat and the illegal pet trade. Despite being the focus of extensive and ongoing behavioral studies, there is comparatively little known about the genetic population structuring of the species. Here, we present the most comprehensive population genetic analysis of ring‐tailed lemurs to date from across their likely remaining geographic range. We assessed levels of genetic diversity and population genetic structure using multilocus genotypes for 106 adult individuals from nine geographically representative localities. Population structure and F ST analyses revealed moderate genetic differentiation with localities being geographically partitioned into northern, southern, western and also potentially central clusters. Overall genetic diversity, in terms of allelic richness and observed heterozygosity, was high in the species (AR = 4.74, H O = 0.811). In fact, it is the highest among all published lemur estimates to date. While these results are encouraging, ring‐tailed lemurs are currently affected by ongoing habitat fragmentation and occur at lower densities in poorer quality habitats. The effects of continued isolation and fragmentation, coupled with climate‐driven environmental instability, will therefore likely impede the long‐term viability of the species. Abstract : Here, we present the most comprehensive population genetic analysis of ring‐tailed lemurs to date from across their likely remaining geographic range. Our study uses multilocus genotypes for 106 adult individuals from nine geographically representative localities to evaluate population genetic diversity and structure on a range‐wide scale. The results described herein demonstrate that, while Madagascar's remaining ring‐tailed lemur populations are geographically isolated, they have retained high levels of genetic diversity, with moderate genetic differentiation among populations despite a relatively large geographic distribution.